Children's cooperation and discrimination in a bilingual province - Philipp Lergetporer; Silvia Angerer; Daniela Glätzle-Rützler; Matthias Sutter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
While discrimination and its economic implications have been studied in many different societies and based on a multitude of attributes like ethnicity, religion, gender, or language, the development of such behavior in children is still poorly understood. Here we present experimental evidence from a bilingual city in Northern Italy on whether the language spoken by a partner in a prisoner s dilemma game affects behavior. We examine how discrimination based on language develops in practically all six- to eleven-year old primary school children in the city. We find that cooperation increases with age and that both in-group favoritism and out-group discrimination emerge as children get older.
Keywords: C93; D03; D64; 330